2020
DOI: 10.1038/s41598-020-68848-9
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization implies no direct causal association between leukocyte telomere length and amyotrophic lateral sclerosis

Abstract: We employed Mendelian randomization (MR) to evaluate the causal relationship between leukocyte telomere length (LTL) and amyotrophic lateral sclerosis (ALS) with summary statistics from genomewide association studies (n = ~ 38,000 for LTL and ~ 81,000 for ALS in the European population; n = ~ 23,000 for LTL and ~ 4,100 for ALS in the Asian population). We further evaluated mediation roles of lipids in the pathway from LTL to ALS. The odds ratio per standard deviation decrease of LTL on ALS was 1.10 (95% CI 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…We did not find further significant associations between genetically predicted TL and other neurodegenerative disease, which also confirms results from previous studies. For instance, two previous MR studies did not find significant causal associations between TL and the risk of PD [21] , ALS and FTD [22] . Additionally, most observational studies showed contradictory results [43] , [44] , [45] .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We did not find further significant associations between genetically predicted TL and other neurodegenerative disease, which also confirms results from previous studies. For instance, two previous MR studies did not find significant causal associations between TL and the risk of PD [21] , ALS and FTD [22] . Additionally, most observational studies showed contradictory results [43] , [44] , [45] .…”
Section: Discussionmentioning
confidence: 90%
“…Previous MR studies have described potential causal effects of genetically predicted TL on the risk of AD [17] , [18] , [19] , [20] . However, other MR studies failed to provide evidence of causal associations between TL and the risk of Parkinson’s disease (PD) [21] or Amyotrophic lateral sclerosis (ALS) [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Second, the proportion of phenotypic variance explained by IV-1 was higher than that explained by IV-2; thus, the statistical power of analysis with IV-1 was 40% higher than that of analysis with IV-2 (Table 1 ). Recently, the study published by Gao et al reported that LTL had no direct causal effect on ALS and suggested that shorter LTL can indirectly reduce ALS risk [ 30 ]. Their study was based on IV-2 and an ALS GWAS involving 37,684 individuals of European ancestry [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the consequence calculated from IV-1 was treated as the main one in our research and con rmed the studies indicating a protective effect of LTL on ALS. Notably, a similar article recently published showed that LTL had no direct causal effect on ALS and suggested that shorter LTL can reduce the risk of ALS indirectly based on IVs from a GWAS on 37,684 individuals of European ancestry [28,29]. The GWAS was a proxy for exposure measured LTL by quantitative PCR and the power of statistics was declared to be less than 30%.…”
Section: Discussionmentioning
confidence: 99%